BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Biological Methodsjor Agricultural Sciences. Authors, S. Sadasivam and A. Manickam, Wiley Eastern Ltd., New Delhi and TNAU, Coimbatore, 1992, 246 pp.